Pyhän kirjan varjo . Shadow of the Holy Book - Halonen, Arto (Halonen, Arto, 2007)
Verzio FF submission When and how is it possible to make hundreds of millions of dollars by the translation and publication of a book which nobody wants to read? Perhaps only in the case of Ruhnama, a book which features the absurd propaganda of the late dictator of Turkmenistan Saparmurad Niyazov Turkmenbashi. Arto Halonen adopts an inimitable investigative approach in this effort to untangle the ties between global corporations and million–dollar contracts in Turkmenistan. Key to this search is Ruhnama, Turkmenbashi's "holy" book. The Finnish director portrays the absurd form of dictatorship in Niyazov's Turkmenistan, and how it contrasts with the reality of the world of tough multinational business, which uses all possible means to win favour with the government and the president. The film shows in detail the sophisticated defence mechanisms of a society which, through erudite press spokespersons and a PR department, presents a strictly positive media image, while at the same time creating a barrier to intrusive questions about unpleasant subjects.